Rahasia Meede dan Amnesia Sejarah: Belajar Memaknai Sejarah Lewat Sastra Populer - Umam, Khothibul (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Rahasia Meede by E.S. Ito is a popular novel with a historical theme that was published in 2007. The novel tells of a treasure hunt using various kinds of characters and events that really happened in the real world. To analyze Rahasia Meede, the approach used is a sociology of literature that assesses text as a mirror of society. The study of the text is not preceded by the study of the structure of the text but directly on the historical and socio-political aspects in the text. The result of his research is to make a treasure hunt story, a historical text can be given to the reader with a new and entertaining perspective.